The Mechanism of Action of Antigen Processing Independent T Cell Epitopes Designed for Immunotherapy of Autoimmune Diseases - Shepard, Ella R.; Wegner, Anja; Hill, Elaine V.; Burton, Bronwen R.; Aerts, Sarah; Schurgers, Evelien; Hoedemaekers, Brecht; Ng, Sky T. H.; Streeter, Heather B.; Jansson, Lotta; Wraith, David C. (Frontiers in Immunology, 2021)
Immunotherapy with antigen-processing independent T cell epitopes (apitopes) targeting autoreactive CD4+ T cells has translated to the clinic and been shown to modulate progression of both Graves’ disease and multiple sclerosis. The model apitope (Ac1-9[4Y]) renders antigen-specific T cells anergic while repeated administration induces both Tr1 and Foxp3+ regulatory cells. Here we address why CD4+ T cell epitopes should be designed as apitopes to induce tolerance and define the antigen presenting cells that they target in vivo. Furthermore, we reveal the impact of treatment with apitopes on CD4+ T cell signalling, the generation of IL-10-secreting regulatory cells and the systemic migration of these cells. Taken together these findings reveal how apitopes induce tolerance and thereby mediate antigen-specific immunotherapy of autoimmune diseases.